A Genome Epidemiological Study of SARS-CoV-2 Introduction into Japan - Tsuyoshi Sekizuka (American Society for Microbiology, 2020)
ABSTRACT After the first case of coronavirus disease 2019 (COVID-19) in Japan on 15 January 2020, multiple nationwide COVID-19 clusters were identified by the end of February. The Japanese government focused on mitigating the emerging COVID-19 clusters by conducting active nationwide epidemiological surveillance. However, an increasing number of cases continued to appear until early April 2020, many with unclear infection routes and no recent history of travel outside Japan. We aimed to evaluate the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) genome sequences from the COVID-19 cases that appeared until early April 2020 and to characterize their genealogical networks in order to demonstrate possible routes of spread in Japan. Nasopharyngeal specimens were collected from patients, and reverse transcription-quantitative PCR tests for SARS-CoV-2 were performed. Positive RNA samples were subjected to whole-genome sequencing, and a haplotype network analysis was performed. Some of the primary clusters identified during January and February 2020 in Japan descended directly from the Wuhan-Hu-1-related isolates from China and other distinct clusters. Clusters were almost contained until mid-March; the haplotype network analysis demonstrated that the COVID-19 cases from late March through early April may have created an additional large cluster related to the outbreak in Europe, leading to additional spread within Japan. In conclusion, genome surveillance has suggested that there were at least two distinct SARS-CoV-2 introductions into Japan from China and other countries. IMPORTANCE This study aimed to evaluate the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) genome sequences from COVID-19 cases and to characterize their genealogical networks to demonstrate possible routes of spread in Japan. We found that there were at least two distinct SARS-CoV-2 introductions into Japan, initially from China and subsequently from other countries, including Europe. Our findings can help understand how SARS-CoV-2 entered Japan and contribute to increased knowledge of SARS-CoV-2 in Asia and its association with implemented stay-at-home/shelter-in-place/self-restraint/lockdown measures. This study suggested that it is necessary to formulate a more efficient containment strategy using real-time genome surveillance to support epidemiological field investigations in order to highlight potential infection linkages and mitigate the next wave of COVID-19 in Japan.